Technology at the Service of the Elderly - Vitor Manuel Costa Pereira Rodrigues (Universidad de La Sabana, 2020)
La tecnología al servicio de los adultos mayores A tecnologia ao serviço das pessoas idosas An increase in longevity almost always implies the manifestation of more health problems, especially chronic diseases. And here, the elderly's well-being and quality of life may be compromised since their level of dependence on others for everyday activities tends to increase and accentuate. Technologies can play a fundamental role in supporting and helping both the elderly -through telepresence robots that reduce their social isolation- and the informal caregiver -by installing a network of sensors that allow programming alarms for changing position and taking medication, for example-. Therefore, technologies can and should be put at the service of the elderly not to replace the human factor, but as a complement thereto. Para citar este editorial / To reference this editorial / Para citar este editorial Rodrigues, VMCP. Technology at the Service of the Elderly. Aquichan. 2020;20(1):e2011. DOI: https://doi.org/10.5294/aqui.2020.20.1.1 Publicado: 13/03/2020